Constitutional Law and Social Change: A Global Perspective - Suratno, Ujang (Politeknik Siber Cerdika Internasional, 2025)
Constitutional law shapes social change, influencing governance, human rights, and democratic resilience across diverse political and cultural contexts. As societies evolve, constitutional frameworks must adapt to emerging challenges, including populism, digital transformation, and global crises such as pandemics and climate change. This study explores the dynamic relationship between constitutional law and social change from a global perspective, examining how legal frameworks respond to and shape societal transformations. The research aims to analyze key constitutional developments worldwide, focusing on constitutional amendments, judicial interpretations, and landmark decisions that reflect societal shifts. Using a qualitative approach, this study synthesizes legal analyses, case studies, and comparative constitutional research to identify patterns in constitutional adaptation across different legal systems. The findings reveal that constitutional law serves as both a catalyst for progressive change and a tool for maintaining stability. While some jurisdictions leverage constitutional mechanisms to advance human rights and democracy, others experience constitutional regression through legalistic autocracy. The study highlights the crucial role of judicial independence, civic engagement, and international legal frameworks in sustaining constitutional resilience amid shifting social dynamics. The research concludes that constitutional law is an evolving instrument that both reflects and influences societal change. By examining global case studies, this study contributes to the discourse on constitutional adaptability, offering insights for policymakers, legal scholars, and human rights advocates on fostering democratic resilience through legal frameworks.